Assessment of IRAP and REMAP markers for evaluation of genetic diversity of eurycoma longifolia / Nor Fadilah Wook - Wook, Nor Fadilah (2018)
Eurycoma longifolia is among the most precious medicinal herbs in Malaysia and due to the current scenario, forest research Institute of Malaysia (FRIM) has started to venture on the plant improvement research of the species.